2015
DOI: 10.1007/s10670-015-9793-3
|View full text |Cite
|
Sign up to set email alerts
|

Ontological Choices and the Value-Free Ideal

Abstract: The aim of this article is to argue that ontological choices in scientific practice undermine common formulations of the value-free ideal in science. First, I argue that the truth values of scientific statements depend on ontological choices. For example, statements about entities such as species, race, memory, intelligence, depression, or obesity are true or false relative to the choice of a biological, psychological, or medical ontology. Second, I show that ontological choices often depend on non-epistemic v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 53 publications
(22 citation statements)
references
References 79 publications
1
21
0
Order By: Relevance
“…In current anthropological theory, emphasis on difference tends to dominate recognition of similarity and many influential anthropologists focus on cases of radical alterity, such as ontological commitments to shamanic transformations (Viveiros de Castro 2014) or thinking forests (Kohn 2013). Ludwig (2016a) has suggested that ethnotaxonomic research provides a different but complementary angle for investigating cross-cultural relations among ontologies. Ethnotaxonomy provides a "bottom-up" strategy that starts with small-scale ontological differences-for instance, concerning categories of animals and plants-rather than the more common anthropological "top-down" strategy that proceeds from the most salient cases of deep ontological difference (Ellen 2006;Hunn 2014).…”
Section: Partial Overlaps In Ontologiesmentioning
confidence: 99%
“…In current anthropological theory, emphasis on difference tends to dominate recognition of similarity and many influential anthropologists focus on cases of radical alterity, such as ontological commitments to shamanic transformations (Viveiros de Castro 2014) or thinking forests (Kohn 2013). Ludwig (2016a) has suggested that ethnotaxonomic research provides a different but complementary angle for investigating cross-cultural relations among ontologies. Ethnotaxonomy provides a "bottom-up" strategy that starts with small-scale ontological differences-for instance, concerning categories of animals and plants-rather than the more common anthropological "top-down" strategy that proceeds from the most salient cases of deep ontological difference (Ellen 2006;Hunn 2014).…”
Section: Partial Overlaps In Ontologiesmentioning
confidence: 99%
“…David Ludwig (2015) has argued that there are non-epistemic values that are relevant with respect to the truth-value of scientific statements such as (1): 'There are two different tiger species in the San Diego zoo'. Here I want to extend his argument, in order to argue that there are non-epistemic values that are relevant with respect to the descriptive project of finding the referent of terms such as 'gender' and 'race'.…”
Section: Reference Explanatory Power and Normative Considerationsmentioning
confidence: 99%
“…More recently, however, there has also been increased attention towards more pragmatic and social considerations that can guide the choice of taxonomic frameworks (Ludwig 2016a). For example, consider that phylogenetic species concepts will often split traditional taxa into several new species.…”
Section: Realism : Convergence Metaphysicians May Suspect That This Nmentioning
confidence: 99%